Relationship Between Counseling Quality and Client Satisfaction in Family Planning at Ika Khairunisa IMP, 2025 - Darsono, Filla Alfazriani; Bonita, Nely; Khairunnisa, Ika (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: The Family Planning (FP) program is a strategic initiative to control population growth and improve women’s reproductive health. The quality of midwife counseling plays a crucial role in enhancing client satisfaction, which may influence contraceptive adherence and overall program success at the Independent Midwifery Practice (IMP) level. Objective: This study aimed to determine the relationship between the quality of midwife counseling and client satisfaction in family planning services at Ika Khairunisa IMP. Method: A quantitative cross-sectional design was employed. The population consisted of active family planning acceptors at Ika Khairunisa IMP, with 80 respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using univariate and Chi-square tests (α = 0.05). Results and Discussion: Most respondents (70%) rated counseling quality as good, and 75% reported being very satisfied. Statistical analysis showed a significant relationship between counseling quality and client satisfaction. Conclusion: Improved counseling quality significantly enhances client satisfaction; therefore, continuous competency development is recommended.